2017
DOI: 10.3390/v9080200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Historic Smallpox Specimens from a Czech Museum

Abstract: Although smallpox has been known for centuries, the oldest available variola virus strains were isolated in the early 1940s. At that time, large regions of the world were already smallpox-free. Therefore, genetic information of these strains can represent only the very last fraction of a long evolutionary process. Based on the genomes of 48 strains, two clades are differentiated: Clade 1 includes variants of variola major, and clade 2 includes West African and variola minor (Alastrim) strains. Recently, the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 37 publications
(51 reference statements)
6
67
0
1
Order By: Relevance
“…The most significant difference between the data presented in Figure 5 and the previous work is that our results push back the date of the tMRCA by about 100 years for all VARVs (from 1588–1645 to 1470–1563), as well as the split of the VARV major and minor clades (from 1734–1793 to 1579–1667). Interestingly, the dates for speciation of all VARV and the major/minor species are midway between those calculated by Duggan et al [ 1 ] and those recently calculated by Pajer et al [ 21 ], who sequenced the VARV-major genome from 1942 and the VARV-minor genome from 1850. The number of unique SNPs associated with particular viruses at nodes on the tree ( Figure 5 ) are consistent for all of the VARVs, suggesting that, after the speciation of VARV, there has been little to no recombination with other poxvirus species.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The most significant difference between the data presented in Figure 5 and the previous work is that our results push back the date of the tMRCA by about 100 years for all VARVs (from 1588–1645 to 1470–1563), as well as the split of the VARV major and minor clades (from 1734–1793 to 1579–1667). Interestingly, the dates for speciation of all VARV and the major/minor species are midway between those calculated by Duggan et al [ 1 ] and those recently calculated by Pajer et al [ 21 ], who sequenced the VARV-major genome from 1942 and the VARV-minor genome from 1850. The number of unique SNPs associated with particular viruses at nodes on the tree ( Figure 5 ) are consistent for all of the VARVs, suggesting that, after the speciation of VARV, there has been little to no recombination with other poxvirus species.…”
Section: Resultsmentioning
confidence: 68%
“…By using the improved assembly of the ancient VARV-VD21 genome together with TATV + CMLV genomes for phylogenetic analysis and the prediction of clade divergence dates, we determined a tMRCA for all VARVs within the range of 1470–1563. This is approximately midway between the latest two estimates from the publications describing the ancient VARV genomes [ 1 , 21 ]. The BEAST software predicted a split of the VARV and CMLV + TATV clades approximately 1250 years prior to the tMRCA for all VARVs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The authors conclude that the loss of gene function seen in modern VARVs compared to some other OPVs must have occurred before 1650 approximately. By calculating phylogenetic trees, the Lithuanian sequence fell basal to all VARV sequences [46,50]. Further analyses revealed that the time scale of VARV evolution is more recent than often supposed-the two major viral lineages diverged within the 18th and 19th centuries.…”
Section: Variola Virus Evolutionmentioning
confidence: 93%
“…Further genomic and historical work will certainly help shed light on the matter, even if no appropriate ancient DNA is forthcoming.93 87 Hawi 47 and 71 (TSM 113 and 121). 88 KJH 14 (TSM [71][72][73]. .…”
Section: Symptoms Of a Plaguementioning
confidence: 99%